2022
DOI: 10.1108/wje-03-2022-0117
|View full text |Cite
|
Sign up to set email alerts
|

Development of efficiency analysis for I-beam steel section with web opening via numerical method

Abstract: Purpose Due to the enormous increase in economic development, structural steel material gives an advantage for the construction of stadiums, factories, bridges and cities building design. The purpose of this study is to investigate the behaviour of bending, buckling and torsion for I-beam steel section with and without web opening using non-linear finite element analysis. Design/methodology/approach The control model was simulated via LUSAS software with the four main parameters which included opening size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A critical study of steel beams with web openings has been investigated, and it is observed that the web openings not only deteriorate the practical section, but also dismiss its continuity [25]. The behavior of buckling, bending, and torsion for steel I beams that have and do not have web opening is studied by using nonlinear finite element analysis using LUSAS software [26]. From this study, it can be concluded that the web openings of square shape have the highest efficiency of structural under buckling.…”
Section: Introductionmentioning
confidence: 99%
“…A critical study of steel beams with web openings has been investigated, and it is observed that the web openings not only deteriorate the practical section, but also dismiss its continuity [25]. The behavior of buckling, bending, and torsion for steel I beams that have and do not have web opening is studied by using nonlinear finite element analysis using LUSAS software [26]. From this study, it can be concluded that the web openings of square shape have the highest efficiency of structural under buckling.…”
Section: Introductionmentioning
confidence: 99%